DAMPAK PERTUMBUHAN EKONOMI SEKTOR PERTANIAN TERHADAP PROFITABILITAS BANK PERKREDITAN RAKYAT DI WILAYAH SULAWESI - wijaya, linda; Al muizuddin Fazaaloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Indonesia, which is known as an agricultural country, needs special attention in the agricultural sector. This is due to the warning of the threat of a global Food Crisis by FAO. In addition, there are capital problems for some actors in the agricultural sector. With one of the financial institutions that has an important role in advancing SMEs is BPR. Therefore, the purpose of this study is to examine the impact of economic growth in the agricultural sector on the profitability of rural banks in the Sulawesi Region. The research used quantitative methods conducted at rural banks in Sulawesi that have been registered with OJK. This study used as many as 14 BPR as samples. Data collection using the purposive sampling method has been registered with OJK and has complete financial statements from 2013-2022. This research uses Panel Data analysis techniques processed through STATA 14. The result of this study is that the GDP of the Agricultural Sector, DPK and CAR does not have a significant and positive effect on the ROA of BPR. NPL has a significant and negative effect on ROA. BOPO has a significant and positive effect on ROA. LDR has no effect and negative effect on ROA Then based on simultaneous tests of PDRB, DPK, CAR, NPL, BOPO and LDR variables have a significant effect on ROA.